Rethinking Moundville and its hinterland (Ripley P. Bullen series, 2016)
Moundville, near Tuscaloosa, Alabama, is one of the largest pre-Columbian mound sites in North America. Comprising twenty-nine earthen mounds, Moundville was a major political and religious centre. A much-needed synthesis of the rapidly expanding archaeological work that has taken place in the region over the past two decades, this volume presents the results of multifaceted research and new excavations.